Hearing loss in type 1 diabetes mellitus: a need to understand precise pathological mechanisms and develop novel therapeutic approaches - Mittal, Rahul; Camick, Nathanael; Lemos, Joana R. N.; Lanzoni, Giacomo; Fraker, Christopher A.; Hirani, Khemraj (Frontiers in Audiology and Otology, 2023)
This integrative review and perspective article synthesizes current knowledge about the co-morbidity of Type 1 Diabetes (T1D) and sensorineural hearing loss (SNHL), affecting an estimated 9.2 per 1,000 T1D patients annually. Combining data from clinical, preclinical, and mechanistic studies, the article elucidates the complex pathological mechanisms contributing to SNHL in T1D. It is established that T1D accelerates age-related SNHL and brings about detrimental changes in the auditory system, including damage to outer hair cells (OHCs), inner hair cells (IHCs), the stria vascularis (SV), and the spiral ligament (SL). Furthermore, T1D-associated peripheral neuropathy, microvascular damage, and chronic inflammation in the inner ear contribute to auditory deficits. Although some consistency exists between animal models and human conditions, notable discrepancies warrant the refinement of preclinical models to more accurately mirror human clinical scenarios. This perspective article highlights the need for targeted research to bridge existing knowledge gaps and accelerate the development of early-stage interventions for SNHL in T1D patients. Advancements in this field hold the promise of enhancing clinical prognosis and improving the quality of life of individuals having T1D.